Usefulness of the additional contrast agents to identify offending nerve root in selective nerve root block. Issue 5 (4th February 2022) - Ko, Sangbong; Nam, Junho; Lee, Jaejun
Abstract : Abstract: It is hypothesized that if it is confirmed that the pain caused by the injection needle coincides with the lower leg radiating pain(LLRP) that the patient mainly complains of, then the contrast agents may be used less. This study aims to understand if the identification of lancinating identical pain in the procedure could replace the use of contrast agents that causes additional pain provocation using control arm of randomized clinical trial. This retrospective study included 165 patients who met exclusion criteria from among patients who underwent Selective nerve root block for the treatment of LLRP. With the identical and lancinating pain confirmed in the same site of the patient, consistent with that of the original symptom, the subjects were divided into 2 groups: 1 without contrast injection (Non-Dye [ND] group; 57 patients) and the other with contrast injection (Dye [D] group; 108 patients). The degree of LLRP in the 2 groups was evaluated using visual analog scale (VAS) before injection, 2, 6, and 12 weeks after injection. Functional outcomes were measured using Owestry Disability Index and Rolland-Morris Disability Questionnair, whereas quality of life was measured using Physical component score and Mental component score of Short Form 36 (SF-36) before injection and 3 months after injection. There was no statistically significant difference in the LLRP severity in both groups at all times and no statistical difference in the degree of VAS improvement relative to the before-injection VAS value between the 2 groups at 2 and 6 weeks after injection (all P > .05). At 12 weeks after injection, there was a statistically significant difference, but they were below Minimum Clinical Important Difference, bearing little clinical implications. There was no statistically significant difference between the 2 groups in Owestry Disability Index, Rolland-Morris Disability Questionnair, SF-36 Physical component score, and SF-36 Mental component score at every interval (all P > .05). Instead of contrast agent injections that have been used for accurate nerve root identification during Selective Nerve Root Block, the method of merely checking if the needle-induced pain under fluoroscopic imaging is consistent with the LLRP that the patient predominantly experiences shows the same effect in the patient's pain control and functional outcome.